3D X-ray CT and diffusion measurements to assess tortuosity and constrictivity in a sedimentary rock - Takahashi, Hiroaki; Seida, Yoshimi; Yui, Mikazu (Diffusion Fundamentals, 2009)
A high-resolution, three-dimensional (3D) image of the interior of the sedimentary rock was obtained by means of nano-focus X-ray computer tomography (X-ray CT). Using computational methods to analyze the 3D microstructure of the rock, we presented the tortuosity and geometrical constrictivity. We also presented results on the tritiated water (HTO) diffusion tests and a mercury intrusion porosimetry (MIP) test performed on the rock. We have compared these results to understand the dominant parameters that control diffusion of HTO in the present system. These results suggest that the dominant parameters in the present system are not the constrictivity but the tortuosity and the diffusion-accessible porosity. The material considered in this study is the siliceous mudstones sampled from 500 m in depth at the Wakkanai formation around Horonobe underground research center in Hokkaido, Japan.